Pengetahuan dan Praktik Keamanan Pangan Ibu di Jakarta Selama Masa Pandemi Covid-19 - Widya Aprilita Minamilail; Lilis Nuraida; Winiati P. Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Many reports revealed that the household is considered as the main contributor for foodborne diseases. Although Covid-19 is not a foodborne diseases, Covid-19 pandemic has forced people to adapt to new habits especially regarding hygiene and sanitaion practices. This may have some implication on behaviour at household level contributing to food safety. The present study aimed to describe food safety knowledge and practices in the households during the Covid-19 pandemic. This study applied an online survey with mothers as respondents and the questionnaire was distributed through social media. Respon-dents were determined purposively with the inclusion criteria: women aged 21-64 years, married, had children, lived or settled in Jakarta for at least one year, and played a role in household food procurement. From the target of 400 respondents, 443 respondents met the requirements for data analysis. The survey results showed that education and income moderately correlated with food safety knowledge and practices. Although more than half of respondents (65.2%) still have inadequate knowledge on food safety and Covid-19, higher number of respondents (71.3%) were considered to have good practices to enhance food safety and prevent Covid-19 infections. During the pandemic there were changes in behaviours as shown by an increase of respondents cooking at home (65.5%) compared to before the pandemic (56.4%) and eating habits in restaurants, which decreased during the pandemic (10.6%) compared to before the pandemic (23.7%). In chosing food source, taste and cleanliness were the main considerations. More than half of the respondents (58.7%) obtained information about COVID-19 and food safety from social media.